Copy number variation across European populations. - Wanting Chen; Caroline Hayward; Alan F Wright; Andrew A Hicks; Veronique Vitart; Sara Knott; Sarah H Wild; Peter P Pramstaller; James F Wilson; Igor Rudan; David J Porteous (PLoS ONE)
Genome analysis provides a powerful approach to test for evidence of genetic variation within and between geographical regions and local populations. Copy number variants which comprise insertions, deletions and duplications of genomic sequence provide one such convenient and informative source. Here, we investigate copy number variants from genome wide scans of single nucleotide polymorphisms in three European population isolates, the island of Vis in Croatia, the islands of Orkney in Scotland and the South Tyrol in Italy. We show that whereas the overall copy number variant frequencies are similar between populations, their distribution is highly specific to the population of origin, a finding which is supported by evidence for increased kinship correlation for specific copy number variants within populations.